Alberto Pérez Calvo - Torres Gutiérrez, Alejandro (Huarte de San Juan. Geografía e Historia, 2014)
This biographical sketch is dedicated to professor Alberto Pérez Calvo, Full professor of Constitutional Law at the Public University of Navarre, during more of two decades. Born in Tudela in 1944, he obtained his PhD in the Faculty of Law of San Sebastian (University of Valladolid). He taught at this Faculty of Law, and in the Faculties of Law of Salamanca, Alcalá, and Public University of Navarre. He had a large international experience in France, Italy, Suisse, Moldavia, Poland, Turkey, Canada, USA, Bolivia, México, and Tunisia. In 2003, he was awarded with the title of Doctor Honoris Causa by the University of Nancy-2 (France). He also developed and intense life as public servant, being General Director of Public Administrations. His main contributions and publications are focused in the study of the States structure, the Autonomous Communities in Spain, the idea of Nation, the Ombudsmans institution, the European Union, and the General Theory of Public Law.
Keywords: Alberto Pérez Calvo; Constitutional Law; biographical sketch; CV; publications